Analysis of bronchovascular patterns in the left superior division segment to explore the relationship between the descending bronchus and the artery crossing intersegmental planes - Li, Zhikai; Zhao, Qingtao; Wu, Wenbo; Hu, Zhonghui; Zhang, Xiaopeng (Frontiers in Oncology, 2023)
Background: A comprehensive understanding of the anatomical variations in the pulmonary bronchi and arteries is particularly essential to the implementation of safe and precise left superior division segment (LSDS) segmentectomy. However, no report shows the relationship between the descending bronchus and the artery crossing intersegmental planes. Thus, the purpose of the present study was to analyze the branching pattern of the pulmonary artery and bronchus in LSDS using three-dimensional computed tomography bronchography and angiography (3D-CTBA) and to explore the associated pulmonary anatomical features of the artery crossing intersegmental planes. Materials and Methods: The 3D-CTBA images of 540 cases were retrospectively analyzed. We reviewed the anatomical variations of the LSDS bronchus and artery and assorted them according to different classifications. Results: Among all 540 cases of 3D-CTBA, there were 16 cases (44.4%) with lateral subsegmental artery crossing intersegmental planes (AX3a), 20 cases (55.6%) Without AX3a in the descending B3a or B3 type, and 53 cases (10.5%) with AX3a, 451 cases (89.5%) Without AX3a in the Without the descending B3a or B3 type. This illustrated that the AX3a was more common in the descending B3a or B3 type (P < 0.005). Similarly, there were 69 cases (36.1%) with horizontal subsegmental artery crossing intersegmental planes (AX1+2c), 122 cases (63.9%) Without AX1+2c in the descending B1+2c type, and 33 cases (9.5%) with AX1+2c, 316 cases (90.5%) Without AX1+2c in the Without the descending B1+2c type. Combinations of the branching patterns of the AX1+2c and the descending B1+2c type were significantly dependent (p < 0.005). The combinations of the branching patterns of the AX1+2c and the descending B1+2c type were frequently observed. Conclusions: This is the first report to explore the relationship between the descending bronchus and the artery crossing intersegmental planes. In patients with the descending B3a or B3 type, the incidence of the AX3a was increased. Similarly, the incidence of the AX1+2c was increased in patients with the descending B1+2c type. These findings should be carefully identified when performing an accurate LSDS segmentectomy.